Development of Key Indicators for Power Supply Companies - Tarasova, Anna (2021)
This article is devoted to the synthesis and analysis of a set of key performance indicators (KPI) for energy companies.  The authors look at several large enterprises operating in the energy sector of Russia to answer the question: what factors play a critical role in the development of KPI for the power supply companies?